2019
DOI: 10.1101/693101
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of housekeeping genes in the peripheral blood of retinoblastoma patients

Abstract: Retinoblastoma is a pediatric neoplasia with a high incidence in non-developed countries. Nowadays the diagnosis is clinical and unfortunately in advanced stages of the diseases, which puts the child´s life risk. The search for molecular diagnosis on retinoblastoma is necessary. Due to their location and tendency to migrate, biopsies of retinoblastoma are not recommended then, peripheral blood samples can be a good source for the search of biomarker. RT qPCR is a sensitive method for gene expression quantifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In the present work, as compared to those of other tissues, greater number of WU-HKGs were relatively constant across all datasets of blood. Studying human peripheral blood, Martínez-Sánchez et al (2019) found Hprt and Tbp as the most reliable genes. They suggested the utilization of Gapdh , B2m , and Rpl13a genes to be avoided.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present work, as compared to those of other tissues, greater number of WU-HKGs were relatively constant across all datasets of blood. Studying human peripheral blood, Martínez-Sánchez et al (2019) found Hprt and Tbp as the most reliable genes. They suggested the utilization of Gapdh , B2m , and Rpl13a genes to be avoided.…”
Section: Resultsmentioning
confidence: 99%
“…Frontiers in Genetics frontiersin.org datasets of blood. Studying human peripheral blood, Martínez-Sánchez et al (2019) found Hprt and Tbp as the most reliable genes. They suggested the utilization of Gapdh, B2m, and Rpl13a genes to be avoided.…”
Section: Figurementioning
confidence: 99%
“…These findings suggest a possible hereditary component; therefore, the mRNA levels of the former genes were measured in family members and compared to the patients. Strikingly, the results indicated a higher level of the p53 mRNA in the family members than in controls [55]. Given the hypothetical diagnostic power of the previously mentioned biomarkers, it would be interesting to develop further validation and implementation in the clinic.…”
Section: Biomarkersmentioning
confidence: 88%
“…Loss of the RB gene can induce apoptosis, representing a mechanism against the proliferation of potentially malignant cells [53]. Cancer cells can then proliferate and overcome the RB1 loss-dependent apoptosis when accompanied by other events such as abrogation of the p53 pathways [54][55][56]. RB also has pro-apoptotic behaviours; indirectly, it was shown that RB can defeat the MDM2-anti-apoptotic function on p53-induced apoptosis in 1999.…”
Section: The Proteinmentioning
confidence: 99%